Polyisophthalamides with Heteroaromatic Pendent Rings: Synthesis, Physical Properties, and Water Uptake - Ferreiro, J.J.; De La Campa, J.G.; Lozano, A.E.; De Abajo, J.
A set of novel aromatic polyamides containing pyridine pendent groups was prepared from aromatic diamines and new monomers that are 5-substituted derivatives of isophthalic acid bearing nicotinamide, isonicotinamide, or picolinamide groups. The polymers were obtained in high yield and high molecular weight by the phosphorylation method of polycondensation. They were characterized by spectroscopic and chromatographic methods and several of their properties were investigated. All of the polymers were soluble in polar aprotic solvents and gave films of good mechanical properties. Glass transition temperatures were higher than that of the reference polymer, poly(m-phenyleneisophthalamide)(IP-MPD), while the thermal resistance, defined by the initial decomposition temperature observed by thermogravimetry, was in the range 370-420 8C, lower by 30-70 8C than that of IP-MPD. The presence of a pendent pyridine group and an additional amide side group per repeat unit made the polymers essentially amorphous and greatly improved their abilities to absorb water in comparison with nonsubstituted polyamides. Water uptake values up to 15
Keywords: COMPUTER MODELING; MONOMERS; POLYAMIDES; STRUCTURE-PROPERTY RELATIONS; SYNTHESIS; THERMAL PROPERTIES; WATER UPTAKE